Alternaria-Brassica pathosystem: development and perspective - Prabhu Dayal Meena; Jameel Akhtar; Ashish Kumar Gupta; Bharat Raj Meena; Samridhi Mehta; Kumari Monika; Govind Singh Saharan; Naresh Mehta (Journal of Oilseed Brassica, 2026)
A sudden outbreak of a plant disease might result in significant economic losses. Understanding the disease triangle,disease epidemics, and forecasting are all crucial in dealing with pathogens. The Genus Alternaria is a notorious fungushaving ~275 species, responsible for enormous economic losses varying from 10% to 70% in crucifers which areconsidered as major edible oil crops all over the world. The Alternaria blight/ black spot disease is the major bottleneckin the global production of commercial oilseed Brassicas. Among Alternaria species, A. brassicae, A. brassicicola, A.raphani, and A. alternata are well-documented for infecting several members of the Brassicaceae family. Recent advancedtaxonomic investigations have yielded a wealth of data that may be used to outline the evolutionary lineages withinAlternaria and related genera. In addition, some R genes/QTLs such as chitinase, endochitinase ‘ech42’, glucanase,PmAMP1, AbVF19, Amr1 etc. from host crop and non-hosts have also been identified through molecular markerstargeting A. brassicae and A. brassicicola. Though the prediction models are available, but their practical utility is stilllimited for effective forewarning. Another problem is the lack of robust data on the potentiality of indigenous as well asexotic genetic resources with a resistance to Alternaria blight making the exploitation of non-host resistance (NHR)mechanisms unfeasible in protecting Brassica crops. The availability of resistant sources is not yet reported in the Utriangle species. Thus, the focus of this review is to identify gaps and bottlenecks in our understanding of the Alternaria-Brassica pathosystem in multiple dimensions which could aptly incorporate in holistic management approach with asustainable and profitable solution to deal with the black spot disease of crucifers.